God, memory and beauty: A Manichaean analysis of Augustine’s Confessions, Book X - Van Oort, Johannes (HTS Teologiese Studies / Theological Studies, 2013)
The article first sketches some main trends in the recent study of Augustine’s Confessions as a work aimed at Manichaean readers. It then detects and analyses the Manichaean-inspired parts in Book X of the Confessions. Augustine’s famous theory of memory seems to be directly inspired by Manichaean concepts such as found in the Coptic Manichaean Kephalaia. The article end with a number of conclusions.